No fim o princípio: raízes de Luuanda - Costa, Eliane Gonçalves da (2007)
The present dissertation aims to study the book of estórias Luuanda, from the Angolan writer José Luandino Vieira, specially, searchs to identify through of the junction space/character, the symbols which constitute the literary city of Luuanda. Bearing in mind conceptions of space, the city and their simbols, our hypothesis point out to the existence of a ritual where characters and space join themselves to prepare the arrival of the new Luuanda city. In these rituals, the organization of the space, the influence from the power of nature are commom in the preparation of the initiates . Reading the stories that compose the book is the same that to read these spaces, its symbols and its symbology. When the author brings the marks of Luanda city in the title, he requests us a new reading from this space already identified - the capital of Angola. This attempt of reading is connected to re-map the city, to create new codes, guided by the characters, who in the Luuanda´s case, are mixtured into the space. Our theorical fundamentation is based primordially, in Lins (1976) who inscribes the character as space; Bakhtin (1993) and Lotman (1978) whose associate time and space (cronotopo). The work is organized in four chapters and try to map Luanda as a real and imaginary city. The dissertation proposes a reading of the city as a space marked by the settling and also as a literary space. Among others conclusions, our research identified Luuanda as a kind of countermap, built by characters-architects, voices from the musseques. Idealized city, Luuanda take in to the consideration the real Luanda, different spaces which join thenselves upon the signs of the freedom